2008
DOI: 10.1152/jn.00065.2008
|View full text |Cite
|
Sign up to set email alerts
|

Median Raphe Stimulation Disrupts Hippocampal Theta Via Rapid Inhibition and State-Dependent Phase Reset of Theta-Related Neural Circuitry

Abstract: Jackson J, Dickson CT, Bland BH. Median raphe stimulation disrupts hippocampal theta via rapid inhibition and state-dependent phase reset of theta-related neural circuitry. J Neurophysiol 99: 3009 -3026, 2008. First published April 24, 2008 doi:10.1152/jn.00065.2008. Evidence has accumulated suggesting that the median raphe (MR) mediates hippocampal theta desynchronization. However, few studies have evaluated theta-related neural circuitry during MR manipulation. In urethane-anesthetized rats, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 61 publications
5
40
0
1
Order By: Relevance
“…37,38 Thus, the serotonergic neurons may not have been able to follow the 24 Hz stimulation during an entire 5-min train. Low-frequency MR stimulation (0.5 Hz) but not high frequency (100 Hz) reportedly causes a statedependent reset of phase of the theta rhythm, 47 which is thought to increase stimulus-processing in hippocampal networks. In cats, the firing rates of serotonergic raphe neurons are directly correlated with arousal, highest during waking, less during slowwave sleep, and least during paradoxical sleep.…”
Section: Physiologic Cellular and Molecular Repair Mechanismsmentioning
confidence: 99%
“…37,38 Thus, the serotonergic neurons may not have been able to follow the 24 Hz stimulation during an entire 5-min train. Low-frequency MR stimulation (0.5 Hz) but not high frequency (100 Hz) reportedly causes a statedependent reset of phase of the theta rhythm, 47 which is thought to increase stimulus-processing in hippocampal networks. In cats, the firing rates of serotonergic raphe neurons are directly correlated with arousal, highest during waking, less during slowwave sleep, and least during paradoxical sleep.…”
Section: Physiologic Cellular and Molecular Repair Mechanismsmentioning
confidence: 99%
“…2), another function of these neurons may be to promote the onset of SIA epochs during SW sleep. Although the neural mechanisms responsible for generating the transient arousal state SIA are largely unknown (Jackson et al 2008;Jarosiewicz et al 2002), it has been shown that the cholinergic system plays an important role: knockout mice without the ␤2-subunit of nicotinic receptors showed decreased frequency of SIA occurrence (Lena et al 2004). This finding not only supports our proposal that the specific neuronal population we identified is likely cholinergic neurons but also suggests that MSvDB cholinergic neurons may be a crucial component of the SIA generation mechanism.…”
Section: New Insights On the Function Of Msvdb Pro-arousal Slow-firinmentioning
confidence: 99%
“…Although the exact targets of MRR are not known in every innervated brain area, MRR projection seems to be very specific in the HIPP and MS. In the HIPP of the rat, MRR establishes synaptic contacts with the somata or proximal dendrites of different types of interneurons, except parvalbumin-positive cells (Freund et al 1990; Acsády et al 1993; Papp et al 1999; Somogyi et al 2004; Varga et al 2009), and MRR provides a complex modulation of the hippocampal network activity (Assaf and Miller 1978; Vertes and Kocsis 1997; Jackson et al 2008). In the MS and diagonal band of Broca of the rat, MRR fibers give perisomatic and per-idendritic baskets onto parvalbumin and calbindin-positive GABAergic cells, specifically (Leranth and Vertes 1999; Aznar et al 2004).…”
Section: Introductionmentioning
confidence: 99%